Fiqh Study on Muslim/Muslimah Clothing and In Relation to the Problem - Maytasya Budiwaluyo; Nazwa Sabrina Naslim (Jurnal Sahabat ISNU SU, 2025)
This study aims to examine the views of Islamic jurisprudence (fiqh) on Muslim and Muslimah clothing and its relationship to the concept of aurat (wārat) in Islamic teachings. This study discusses the boundaries of male and female aurat according to various schools of Islamic jurisprudence, and how these provisions are applied in the form of clothing that complies with Islamic law. This study uses a qualitative approach with a literature study method of primary sources such as the Qur'an, Hadith, and classical and contemporary fiqh books. The results of the study indicate that clothing in Islam is not only a protection for the body, but also a reflection of a Muslim's obedience to the commands of Allah SWT. Clothing that completely covers the aurat, is not transparent, not tight, and does not resemble the opposite sex is the main requirement for clothing according to Islamic jurisprudence. In addition, this study also highlights the modern challenges in understanding the boundaries of aurat amidst the currents of fashion and globalization. This research is expected to provide a deeper understanding for Muslims in implementing Islamic values ​​in clothing wisely and in accordance with the current context.